All‐optical time‐domain demultiplexing of 170.8 Gbit/s signal in chalcogenide GeAsSe microstructured fibre. Issue 2 (1st January 2013) - Le, S.D.; Gay, M.; Bramerie, L.; Chartier, T.; Thual, M.; Simon, J.‐C.; Brilland, L.; Méchin, D.; Toupin, P.; Troles, J.
Abstract : A report is presented on four‐wave‐mixing‐based all‐optical time‐domain demultiplexing of a 170.8 Gbit/s signal down to 42.7 Gbit/s in a chalcogenide GeAsSe microstructured fibre. The high nonlinearity of the fibre allows error‐free and low power penalty operation with only 56 mW of total input average power.